TCF21/POD-1, a Transcritional Regulator of SF-1/NR5A1, as a Potential Prognosis Marker in Adult and Pediatric Adrenocortical Tumors - Passaia, Barbara dos Santos; Dias, Matheus Henrique; Kremer, Jean Lucas; Antonini, Sonir Roberto Rauber; Almeida, Madson Queiroz de; Fragoso, Maria Candida Barisson Villares; Lotfi, Claudimara Ferini Pacicco (Frontiers in Endocrinology, 2018)
With recent progress in understanding the pathogenesis of adrenocortical tumors (ACTs), identification of molecular markers to predict their prognosis has become possible. TCF21/POD-1 is a transcriptional regulatory protein expressed in mesenchymal cells at sites of epithelial-mesenchymal transition during the development of different systems. Adult carcinomas express less TCF21 than adenomas; genes negatively correlated with TCF21 include among others BUB1B in KEGG (Encyclopedia of genes and Genomes) pathway analysis. The difference between BUB1B and PINK1 expression has been described previously to be associates with survival in adult but not pediatric carcinomas. Here, we analyzed the gene expression of TCF21, BUB1B, PINK1 and NR5A1 in adult and pediatric ACTs. We found a negative correlation between the relative expression levels of TCF21 and BUB1B in adult ACTs, but the relative expression levels of TCF21, BUB1B, PINK1 and NR5A1 were similar in childhood adrenocortical tumors. In addition, we propose using the subtracted expression levels of the TCF21-BUB1B genes as a predictor of overall survival in adult carcinomas and TCF21-NR5A1 as a predictor of malignancy for pediatric tumors in patients aged < 5 years. These results require further validation in different cohorts of both adult and pediatric samples. Finally, we observed that the overall survival for patients aged < 5 years was markedly favorable compared with that for patients > 5 years as well as adult patients with carcinoma. In summary, we propose TCF21/POD-1 as new prognostic marker in adult and pediatric adrenocortical tumors.